Method for preparing hard carbon negative material from zinc chloride activated lignite and application thereof in sodium ion battery

CN122897406APending Publication Date: 2026-10-13ZHALAI NUOER COAL IND CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611093826.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,目前尚未有关于采用ZnCl2活化褐煤制备钠离子电池硬碳负极材料的系统研究

Benefits of technology

[0014]1、极低活化温度:利用ZnCl2的脱水催化和熔融渗透作用,可在500~900℃的低温条件下实现褐煤的高效炭化和活化,相比FeCl3(700~1100℃)和传统硬碳制备(≥1300℃)进一步降低了能耗。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897406A_ABST
    Figure CN122897406A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing lignite-derived hard carbon negative material by zinc chloride activation and application of the lignite-derived hard carbon negative material in sodium ion batteries. First, the lignite is pretreated by washing, drying, crushing and the like to remove surface impurities, then anhydrous zinc chloride is used as an activator, mixed with the lignite, and subjected to one-step carbonization / activation treatment, and finally, the lignite-derived hard carbon negative material with good sodium storage performance is obtained by purifying the lignite through dilute acid washing. The method promotes the lignite to undergo dehydration and polycondensation reaction by virtue of the dehydration of ZnCl2 at high temperature and the Lewis acid catalytic characteristics, inhibits the ordered graphitization of the carbon layer, and forms rich microporous and mesoporous structures by chemical activation to expand the carbon layer spacing. The application uses the low-cost lignite as raw material, adopts the one-step activation method of ZnCl2, and has the advantages of simple preparation process, low activation temperature and low cost. The lignite-based hard carbon negative material prepared by the method has high initial coulombic efficiency, high reversible specific capacity and excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion batteries and relates to a method for preparing sodium-ion anode materials, specifically a method for preparing hard carbon anode materials by activating lignite with zinc chloride and its application in sodium-ion batteries. Background Technology

[0002] Sodium-ion batteries, due to their abundant sodium resources, low cost, and good safety, have shown broad application prospects in the field of large-scale energy storage. Hard carbon materials, with their advantages of high sodium storage capacity and good cycle stability, are considered the most commercially promising anode material for sodium-ion batteries. Currently, the precursors for hard carbon mainly include biomass (coconut shells, straw, fruit shells, etc.), resins, and coal-based raw materials. Among them, lignite, as a low-rank coal, is abundant and extremely inexpensive (approximately 100-300 yuan / ton), making it an ideal precursor for preparing hard carbon anodes.

[0003] Chemical activation is an effective means of controlling the pore structure of carbon materials. Commonly used activators include KOH, NaOH, ZnCl2, and H3PO4. Among them, ZnCl2, as a mild chemical activator, has the following unique advantages: (1) Dehydration: ZnCl2 can act as a strong dehydrating agent at high temperatures, promoting the removal of hydrogen and oxygen in the precursor in the form of water, leaving a carbon-rich skeleton; (2) Lewis acid catalysis: ZnCl2, as a Lewis acid, can catalyze the cross-linking reaction of carbon precursors, inhibit graphitization, and promote the formation of disordered structures; (3) Pore-forming effect: ZnCl2 can be embedded in the carbon interlayer during carbonization, and after acid washing, it forms a rich microporous structure; (4) Low activation temperature: The optimal activation temperature of ZnCl2 is usually 500~900℃, which is much lower than that of KOH activation (700~1000℃), and the energy consumption is lower. However, there is currently no systematic study on the preparation of hard carbon anode materials for sodium-ion batteries using ZnCl2 to activate lignite. Summary of the Invention

[0004] This invention provides a method for preparing hard carbon anode materials from lignite activated with zinc chloride and its application in sodium-ion batteries. This method utilizes the dehydration effect of ZnCl2 at high temperatures and the catalytic properties of Lewis acids to promote the dehydration and condensation reaction of lignite, inhibiting the ordered graphitization of the carbon layers. Simultaneously, chemical activation forms abundant microporous and mesoporous structures, expanding the interlayer spacing. This invention uses inexpensive lignite as raw material and employs a one-step ZnCl2 activation method. The preparation process is simple, with low activation temperature and low cost, achieving high-value utilization of low-rank coal resources. This method can produce lignite-based hard carbon anode materials with high initial coulombic efficiency, high reversible specific capacity, and excellent cycle stability.

[0005] The objective of this invention is achieved through the following technical solution:

[0006] A method for preparing hard carbon anode materials from lignite activated with zinc chloride involves first pre-treating the lignite by washing, drying, and crushing to remove surface impurities. Then, anhydrous zinc chloride is used as an activator, mixed with the lignite, and subjected to a one-step carbonization / activation treatment. Finally, the mixture is purified by washing with dilute acid to obtain lignite-derived hard carbon anode materials with good sodium storage performance. The method includes the following steps:

[0007] Step (1) Pretreatment: The lignite is ultrasonically washed sequentially with deionized water and anhydrous ethanol to remove impurities from the surface of the material. After ultrasonic treatment, it is dried in a forced-air drying oven. The dried lignite is then crushed to obtain lignite powder, wherein: the lignite is low-rank lignite with a carbon content of 50-70 wt%, a volatile matter content of 25-45 wt%, and an ash content of 5-20 wt%; the ultrasonic washing time is 0.5-2 h; the drying temperature is 60-80℃ and the time is 6-12 h.

[0008] Step (2) Mixing: Mix the lignite powder obtained in step (1) with anhydrous zinc chloride evenly, wherein: the mass ratio of lignite powder to anhydrous zinc chloride is 1:0.5~1:5, preferably 1:1~1:3; the lignite powder is sieved through a 30~50 mesh sieve, and the anhydrous zinc chloride powder is sieved through a 50~100 mesh sieve;

[0009] Step (3) Carbonization / Activation: The mixed powder obtained in step (2) is placed in a tube furnace, a protective gas is introduced, and carbonization is carried out. After the tube furnace is cooled to room temperature, the carbonization product of lignite is obtained, wherein: the protective gas is nitrogen or argon, the heating rate is 1~10℃ / min, preferably 2~8℃ / min, the carbonization temperature is 500~900℃, preferably 600~850℃, and the holding time is 1~5 h, preferably 2~4 h;

[0010] Step (4) Acid washing and purification: The carbonized product obtained in step (3) is transferred to a dilute hydrochloric acid or dilute sulfuric acid solution and stirred. Then, it is washed with deionized water and filtered until pH=7. Finally, the material obtained by filtration is placed in a drying oven to dry, and lignite-derived hard carbon anode material is obtained. The concentration of dilute hydrochloric acid or dilute sulfuric acid is 0.1~1.0 mol / L, the stirring time is 6~24 h, preferably 8~16 h, the stirring speed is 200~400 rpm, the drying temperature is 100~150℃, and the time is 8~16 h. The specific surface area of ​​the lignite-derived hard carbon anode material is 500~1100 m². 2 / g, with interlayer spacing of 0.37~0.41 nm and average pore size of 1.8~3.8 nm.

[0011] Application of a lignite-derived hard carbon anode material prepared by the above method in the anode of sodium-ion batteries.

[0012] The design concept of this invention is: using lignite as a carbon precursor and anhydrous zinc chloride as an activator. ZnCl2 is in a molten state at high temperature (melting point of 290℃ and boiling point of 732℃), and can fully penetrate into the pores and carbon layers of lignite. Its activation mechanism mainly includes the following aspects: (1) Dehydration: ZnCl2, as a strong dehydrating agent, can promote the removal of hydroxyl groups in lignite, form a cross-linked structure, and inhibit the orderly stacking of carbon layers; (2) Lewis acid catalysis: ZnCl2 catalyzes the condensation reaction of aromatic compounds in lignite, promoting the formation of a three-dimensional disordered carbon network; (3) Template pore formation: Molten ZnCl2 fills the pores of the carbon skeleton, and after acid washing, it leaves rich micropores and mesoporous structures; (4) Inhibition of tar formation: ZnCl2 can promote the cross-linking polymerization of volatile substances and improve carbon yield. By adjusting the ratio of ZnCl2 to lignite, as well as the carbonization temperature and time, precise control over the hard carbon pore structure and interlayer spacing can be achieved, thereby obtaining excellent sodium storage performance.

[0013] Compared with the prior art, the present invention has the following advantages:

[0014] 1. Extremely low activation temperature: By utilizing the dehydration catalysis and melt permeation effect of ZnCl2, efficient carbonization and activation of lignite can be achieved at low temperatures of 500~900℃, which further reduces energy consumption compared with FeCl3 (700~1100℃) and traditional hard carbon preparation (≥1300℃).

[0015] 2. Mild activation conditions: ZnCl2 activation does not require strong oxidation or strong reduction conditions, has low corrosiveness to equipment, and is highly safe.

[0016] 3. High specific surface area: By optimizing the ratio of ZnCl2 to lignite, a specific surface area as high as 500~1100 m² can be obtained. 2 / g of porous hard carbon material provides abundant active sites for sodium storage.

[0017] 4. Excellent electrochemical performance: The prepared lignite-based hard carbon anode material has a large interlayer spacing (0.37~0.41nm), abundant pore structure and defect sites. The reversible capacity reaches 270~310 mAh / g at a current density of 20 mA / g, the initial coulombic efficiency is 80~87%, and the capacity retention is >85% after 1000 cycles at a current density of 1 A / g.

[0018] 5. Cost advantage: ZnCl2 is priced at approximately 6,000 to 8,000 yuan per ton, which is between FeCl3 (3,000 to 5,000 yuan per ton) and CuCl2 (15,000 to 20,000 yuan per ton), making it a high-value product overall. Attached Figure Description

[0019] Figure 1This is a transmission electron microscope (TEM) image of the lignite-based hard carbon anode material for sodium-ion batteries prepared in Example 1.

[0020] Figure 2 The first charge-discharge curve of the lignite-based hard carbon anode material prepared in Example 1 at a current density of 20 mA / g is shown.

[0021] Figure 3 The graph shows the cycling performance of the lignite-based hard carbon anode material prepared in Example 1 at a current density of 1 A / g. Detailed Implementation

[0022] The technical solution of the present invention will be further described below with reference to the accompanying drawings, but it is not limited thereto. Any modifications or equivalent substitutions to the technical solution of the present invention that do not depart from the spirit and scope of the technical solution of the present invention should be covered within the protection scope of the present invention.

[0023] Example 1

[0024] This embodiment provides a method for preparing hard carbon anode materials by activating lignite with zinc chloride, the method comprising the following steps:

[0025] (1) Pretreatment: The lignite (carbon content of about 62 wt%, ash content of about 14 wt%, and volatile matter of about 36 wt%) was ultrasonically washed with deionized water and anhydrous ethanol for 0.5 h respectively to remove impurities from the surface of the material. After ultrasonic treatment, it was placed in a forced-air drying oven and dried at 70℃ for 10 h. The dried lignite was crushed and passed through a 40-mesh sieve to obtain lignite powder.

[0026] (2) Mixing: Mix the lignite powder obtained in step (1) with anhydrous zinc chloride (analytical grade, passed through an 80-mesh sieve) at a mass ratio of 1:2, and grind it thoroughly in a mortar for 15 min to make it evenly mixed.

[0027] (3) Carbonization / activation: Place the mixed powder obtained in step (2) in a magnetic boat, transfer it into a tube furnace, introduce nitrogen gas (flow rate 100 mL / min), heat it to 750℃ at a heating rate of 5℃ / min, keep it at a constant temperature for 3 h, and take out the carbonized product after the tube furnace has cooled to room temperature naturally.

[0028] (4) Acid washing and purification: The carbonized product obtained in step (3) was transferred into a 0.5 mol / L hydrochloric acid solution with a solid-liquid ratio of 1:10 and stirred for 12 h (300 rpm). Then, it was washed with deionized water and filtered until pH=7. Finally, the material obtained by filtration was placed in a vacuum drying oven and dried at 120℃ for 12 h to obtain lignite-derived hard carbon anode material, labeled as HC-1.

[0029] Figure 1This is a transmission electron microscope (TEM) image of the lignite-based hard carbon anode material for sodium-ion batteries prepared in this embodiment. Figure 1 It can be seen that the hard carbon material obtained by this method has the following structural characteristics: 1) it is generally amorphous; 2) the graphite microcrystals are stacked in a turbine-like layered structure with short-range order and long-range disorder; 3) the structure contains abundant defect sites and closed pores. Most importantly, the carbon interlayer spacing is expanded to approximately 0.39 nm. This unique microstructure is considered to be the main structural basis for the reversible insertion / extraction of sodium ions and their contribution to capacity.

[0030] Figure 2 This is the first charge-discharge curve of the lignite-based hard carbon anode material prepared in this embodiment at a current density of 20 mA / g. Figure 2 It can be seen that the coal-based hard carbon material prepared in this embodiment has an initial coulombic efficiency of ≥83% and an initial reversible specific capacity of ≥310 mAh / g.

[0031] Figure 3 This is a graph showing the cycling performance of the lignite-based hard carbon anode material prepared in this embodiment at a current density of 1 A / g. Figure 3 It can be seen that the capacity retention rate after 1000 cycles is >85%.

[0032] Example 2

[0033] The difference between this embodiment and Embodiment 1 is that in step (2), the mass ratio of lignite powder to anhydrous zinc chloride is 1:1. The resulting material is labeled as HC-2.

[0034] Example 3

[0035] The difference between this embodiment and Embodiment 1 is that in step (2), the mass ratio of lignite powder to anhydrous zinc chloride is 1:3. The resulting material is labeled as HC-3.

[0036] Example 4

[0037] The difference between this embodiment and Embodiment 1 is that the carbonization temperature in step (3) is 650°C. The resulting material is labeled as HC-4.

[0038] Example 5

[0039] The difference between this embodiment and Embodiment 1 is that in step (3), the carbonization temperature is 850°C. The resulting material is labeled HC-5.

[0040] Example 6

[0041] The difference between this embodiment and Embodiment 1 is that in step (4), acid washing and purification are performed using a 0.5 mol / L sulfuric acid solution. The resulting material is labeled as HC-6.

[0042] Application Example 1: Electrochemical Performance Testing

[0043] (1) Electrode preparation: The hard carbon sample prepared in Example 1 was ground into fine particles and sieved through a 300-mesh sieve. The active material, conductive agent (super P), and binder (2% sodium alginate) were mixed in a mass ratio of 8:1:1, and an appropriate amount of deionized water was added and ground evenly to obtain an electrode slurry. The slurry was evenly coated on aluminum foil and dried in a vacuum oven at 90°C for 12 hours, and then cut into 10 mm circular electrode sheets.

[0044] (2) Sodium-ion half-cell assembly: Using metallic sodium as the counter electrode, 1M NaPF6+DEGDME as the electrolyte, and glass fiber (GF / C) as the separator, the CR2032 button cell was assembled in an argon-protected glove box.

[0045] (3) Electrochemical performance testing: The electrochemical performance of the battery was tested using a LAND CT2001 A tester. The charge / discharge voltage range was 0~2.5 V (vs. Na). + The first charge-discharge curves were tested at a current density of 20 mA / g, and the cycling performance was tested at a current density of 1 A / g. The prepared coal-based hard carbon material had an initial coulombic efficiency of ≥83%, an initial reversible specific capacity of ≥310 mAh / g, and a capacity retention of >85% after 1000 cycles.

Claims

1. A method for preparing hard carbon anode materials by activating lignite with zinc chloride, characterized in that... The method includes the following steps: Step (1) Pretreatment: The lignite is ultrasonically washed with deionized water and anhydrous ethanol in sequence to remove impurities from the surface of the material. After ultrasonic treatment, it is placed in a forced-air drying oven to dry. The dried lignite is then crushed to obtain lignite powder. Step (2) Mixing: Mix the lignite powder obtained in step (1) with anhydrous zinc chloride until homogeneous; Step (3) Carbonization / Activation: The mixed powder obtained in step (2) is placed in a tube furnace, a protective gas is introduced, and carbonization is carried out. After the tube furnace is cooled to room temperature, the carbonization product of lignite is obtained. Step (4) Acid washing and purification: The carbonized product obtained in step (3) is transferred into dilute hydrochloric acid or dilute sulfuric acid solution and stirred. Then, it is washed with deionized water and filtered until pH=7. Finally, the material obtained by filtration is placed in a drying oven to dry, and lignite-derived hard carbon anode material is obtained.

2. The method for preparing hard carbon anode materials by activating lignite with zinc chloride according to claim 1, characterized in that... In step (1), the lignite is low-rank lignite with a carbon content of 50-70 wt%, a volatile matter content of 25-45 wt%, and an ash content of 5-20 wt%; the ultrasonic washing time is 0.5-2 h; the drying temperature is 60-80℃ and the time is 6-12 h.

3. The method for preparing hard carbon anode materials by activating lignite with zinc chloride according to claim 1, characterized in that... In step (2), the mass ratio of lignite powder to anhydrous zinc chloride is 1:0.5 to 1:5; the lignite powder is sieved through a 30-50 mesh sieve, and the anhydrous zinc chloride powder is sieved through a 50-100 mesh sieve.

4. The method for preparing hard carbon anode material by activating lignite with zinc chloride according to claim 3, characterized in that... The mass ratio of the lignite powder to anhydrous zinc chloride is 1:1 to 1:

3.

5. The method for preparing hard carbon anode materials by activating lignite with zinc chloride according to claim 1, characterized in that... In step (3), the protective gas is nitrogen or argon, the heating rate is 1~10℃ / min, the carbonization temperature is 500~900℃, and the holding time is 1~5 h.

6. The method for preparing hard carbon anode material by activating lignite with zinc chloride according to claim 5, characterized in that... The heating rate is 2~8℃ / min, the carbonization temperature is 600~850℃, and the holding time is 2~4 h.

7. The method for preparing hard carbon anode material by activating lignite with zinc chloride according to claim 1, characterized in that... In step (4), the concentration of dilute hydrochloric acid or dilute sulfuric acid is 0.1~1.0 mol / L, the stirring time is 6~24 h, the stirring speed is 200~400 rpm, the drying temperature is 100~150℃, and the drying time is 8~16 h.

8. The method for preparing hard carbon anode materials by activating lignite with zinc chloride according to claim 7, characterized in that... The stirring time is 8~16 h.

9. A lignite-derived hard carbon anode material prepared by the method according to any one of claims 1-8.

10. The application of a lignite-derived hard carbon anode material prepared by the method of any one of claims 1-8 in a sodium-ion battery anode.